Investigating the Role of P311 in the Hypertrophic Scar - Tan, Jianglin (Public Library of Science, 2010)
The mechanisms of hypertrophic scar formation are not fully understood. We previously screened the differentially expressed genes of human hypertrophic scar tissue and identified P311 gene as upregulated. As the activities of P311 in human fibroblast function are unknown, we examined the distribution of it and the effects of forced expression or silencing of expression of P311. P311 expression was detected in fibroblast-like cells from the hypertrophic scar of burn injury patients but not in peripheral blood mononuclear cells, bone marrow mesenchymal stem cells, epidermal cells or normal skin dermal cells. Transfection of fibroblasts with P311 gene stimulated the expression of alpha-smooth muscle actin (α-SMA), TGF-β1 and α1(I) collagen (COL1A1), and enhanced the contraction of fibroblast populated collagen lattices (FPCL). In contrast, interference of fibroblast P311 gene expression decreased the TGF-β1 mRNA expression and reduced the contraction of fibroblasts in FPCL. These results suggest that P311 may be involved in the pathogenesis of hypertrophic scar via induction of a myofibroblastic phenotype and of functions such as TGF-β1 expression. P311 could be a novel target for the control of hypertrophic scar development.